Praññʻ sūʹ ʼa lupʻ sa māʺ koṅʻcī myāʺ e* lupʻ ṅanʻʺ lamʻʺ ññvhanʻ - Moṅʻ Rvhe (Ba hui Praññʻ sūʹ ʼA lupʻ sa māʺ Koṅʻcī, 1967)
Transcript of speeches delivered at the meetings on discussion of procedures for the people's workers council's to organize the trade-unions in Burma.